Evaluation of routine magnetic resonance imaging of patients with chronic orofacial pain. Issue 1 (January 2019) - Devine, M.; Rahman, N.; Connor, S.E.J.; Patel, J.; Renton, T.
Abstract: The aim of this study was to evaluate the reported presence of magnetic resonance imaging (MRI) pathologies (demyelination, space-occupying lesions, or trigeminal neurovascular contact within the transition zone) in patients with orofacial pain. Patient histories, demographic characteristics, and clinical features were compared between those with and without a reported MRI pathology. A retrospective service evaluation of all patients who had undergone MRI scanning to aid the diagnosis of orofacial pain conditions between 2012 and 2016 was conducted. Data were collected and statistical analyses (frequency and descriptive) performed. One hundred and twenty-five patients (34 male and 91 female) with a mean age of 50 years were included. MRI pathologies included space-occupying lesions (2.4%), trigeminal neurovascular contact (22.4%), other pathology including small vessel cerebrovascular disease (20%), pineal cyst (1.6%), sinus pathologies (1.6%), and degenerative changes to the cervical spine (0.8%). This study found that patients with a provisional diagnosis of trigeminal neuralgia or trigeminal autonomic cephalalgia, as well as patients with elicited pain, were more likely to have abnormal findings on MRI scanning.